Phase-preserved macroscopic visible-light carpet cloaking beyond two dimensions - Chu, Chia-Wei (2015)
Transformation optics, a recent geometrical design strategy of light manipulation with both ray trajectories and optical phase controlled simultaneously, promises an invisibility cloaking device that can render a macroscopic object invisible even to a scientific instrument measuring optical phase. Recent “carpet” cloaks have extended their cloaking capability to broadband frequency ranges and macroscopic scales, but they only demonstrated the recovery of ray trajectories after passing through the cloaks, while whether the optical phase would reveal their existence still remains unverified. In this paper, a phase-preserved macroscopic visible-light carpet cloak is demonstrated in a geometrical construction beyond two dimensions. As an extension of previous two-dimensional (2D) macroscopic carpet cloaks, this almost-three-dimensional carpet cloak exhibits three-dimensional (3D) invisibility for illumination near its center (i.e. with a limited field of view), and its ideal wide-angle invisibility performance is preserved in multiple 2D planes intersecting in the 3D space. Optical path length is measured with a broadband pulsed-laser interferometer, which provides unique experimental evidence on the geometrical nature of transformation optics.